Ice dynamics preceding catastrophic disintegration of the floating part of Jakobshavn Isbræ, Greenland - Johnson, Jesse V.; Prescott, Paul R.; Hughes, Terence J. (Journal of glaciology, 2004)
The floating terminal of Jakobshavn Isbræ, the fastest Greenland ice stream, has disintegrated since 2002, resulting in a doubling of ice velocity and rapidly lowering inland ice elevations. Conditions prior to disintegration were modeled using control theory in a plane-stress solution, and the Missoula model of ice-shelf flow. Both approaches pointed to a mechanism that inhibits ice flow and that is not captured by either approach. Jamming of flow, an inherent property of granular materials passing through a constriction (Jakobshavn Isfjord), is postulated as the mechanism. Rapid disintegration of heavily crevassed floating ice accompanies break-up of the ice jam.